An assessment of states’ websites in Malaysia: an evaluative study - Mohammed Yasin, Nazreena; Abdul Hamid, Rohana; Mohd Adnan, Normala (Kulliyah of Islamic Revealed Knowledge and Human Sciences, IIUM, 2023)
E-government has emerged as one of the government agenda, and it has become part and parcel of Malaysia’s government since its initiation in 1995. The implementation of e-government in Malaysia has started with the establishment of Multimedia Super Corridor (MSC) in 1996 which can give many benefits to the society. Tun Dr Mahathir himself launched the e-government initiative in 1997 after the establishment of ICT. E-government is one of the seven flagships of the Multimedia Super Corridor (MSC) initiative and it plays a role in improving the internal management of the government administration and communications.